Suasana Kerja dan Pengaruh Kepemimpinan dalam Konteks Pendidikan Dasar - Mieske Theresia Tulung; Laurens Kaluge (Jurnal Pendidikan dan Kebudayaan, 2012)
This study aimed at discovering the leadership perception in conditioning the working climate at schools. Three objectives of the aim were describing working climate, teachers’ perception on leadership, and the causal relationship between them. The cluster proportionate random sampling obtained 386 teachers from 24 state and private junior-secondary-schools in the city of Manado. Data were collected through questionnaire administration and analyzed using descriptive and inferential methods. Eight leadership constructs and two working climate were proven to be valid and reliable. Using range criteria of 0-4, the averages of working climate were 2.9 and 2.8 for working spirit and creative climate. On the other hand, using the same criteria, the average of the eight leadership sub-scales ranged between 2.55 and 3.19. The regression analyses found that not all of the leadership components were significant factors for developing the school working climate. Disciplining, listening, and supporting were significant factors for teachers’ working spirit. Whereas, the creative climate of teachers was affected significantly by disciplining, listening, supporting, and empowering factors. The results would be of benefit for educational policies and school improvement.